ACUTE EFFECT OF ADMINISTRATION OF PROPRANOLOL ON ANTIDEPRESSANT EFFECT OF ALPRAZOLAM IN ALBINO MICE - JOHAN PANDIAN J; KINGSHUK LAHON; LAVAKUMAR S (International Journal of Pharma and Bio Sciences, 2012)
Depression is an affective disorder characterized by change of mood and often co-exists with anxiety in depressed patients. Alprazolam, a benzodiazepine anxiolytic, also has antidepressant activity and can be used in Mixed Anxiety and Depressive Disorder. Propranolol, a non-selective beta adrenergic blocker, may be used as adjuvant to benzodiazepines in treatment resistant cases of anxiety. We wanted to know the effect of administration of propranolol on the antidepressant effect of alprazolam in animal models of depression using ‘Behavioural despair.’ Thirty six adult albino mice of either sex were divided into six groups of six animals each and subjected to Tail suspension test (TST) and Forced swim test (FST) and evaluated for cumulative duration of immobility. Then, groups A through F received distilled water (1ml/kg), imipramine (10mg/kg), propranolol (1mg/kg), alprazolam (5mg/kg), propranolol (1mg/kg) + alprazolam (5mg/kg) and propranolol (1mg/kg) + imipramine (10mg/kg) intraperitoneally. TST and FST were repeated. Statistical analysis was done using one way ANOVA, followed by Dunnett’s multiple comparison test, with P< 0.05 as level of significance at 95% confidence intervals. Results were expressed as Mean ± SEM. Administration of drugs decreased the baseline cumulative duration of immobility in some groups in both TST and FST, but there was significant difference between baseline and post-drug administration values only in FST. Day 1 FST results revealed that only imipramine and alprazolam groups showed significant antidepressant activity compared to control. Combination of alprazolam and propranolol and imipramine and propranolol groups showed no significant antidepressant activity compared to control. Hence, acute administration of propranolol with alprazolam and with imipramine probably reversed the significant antidepressant activity which was seen after administration of alprazolam and imipramine alone.